Sensitivity Analysis and Small-Signal Stability of Grid Following Converters - Simón Sepúlveda García; Alejandro Garcés (TecnoLógicas, 2022)
This article presents a small-signal study, based on a sensitivity analysis, of a voltage source converter (VSC) operating as a grid-following device. This type of operation is standard for integrating distributed energy resources directly into a primary grid without considering the control over specific variables (e.g., voltage and frequency), thus maximizing the amount of injected active power. The present study adopted the classical vector-oriented control based on the linearization method of the averaged model; hence, this analysis is limited to linear controls. The main objective of this study is to evaluate how each controller parameter influences the system’s stability. To conduct the sensitivity analysis, an averaged model in the dq reference frame of the VSC was employed to describe the system dynamics in the equivalent state-space model. Afterward, the stability was analyzed through a sensitivity analysis of the eigenvalues of the corresponding state matrix. The numerical results demonstrate that the main problems for the stability of VSCs operating as grid-following converters are threefold: a high value of the filter inductance, a non-ideal impedance that appears depending on the connection point, and poor coordination of the parameters of the Kp controllers. These results are compared to a simple bifurcation analysis of the state matrix, which consists of a diagram that describes the variation in eigenvalues when a parameter changes, thus proving their validity.